The effect of childhood multilingualism and bilectalism on implicature understanding - Antoniou, Kyriakos; Katsos, Napoleon (My University, 2017)
The present study compares the performance of multilingual children speaking Cypriot Greek, Standard Modern Greek, and English (and sometimes an additional language), bilectal children speakers of Cypriot Greek and Standard Modern Greek, and Standard Modern Greek-speaking monolingual children on a task that measures the comprehension of different types of implicature. Despite lower scores in language ability in the target language, multilingual and bilectal children performed at rates comparable to the monolinguals with implicature. Regression analyses indicated a positive correlation between implicature, language proficiency, and age (but not executive control), albeit language ability did not affect implicature within multilinguals. We suggest an interpretation according to which multilingual, bilectal, and monolingual children maintain a comparable level of implicature understanding, but they do so by relying on different resources. Finally, a principal component analysis on different implicature types revealed a single factor of implicature performance. This outcome has implications for pragmatic theory.